Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12964-022-00822-6
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of mutual relationship between malignant hematologic cells and mesenchymal stem cells: Does it contradict the nursing role of mesenchymal stem cells?

Abstract: Mesenchymal stem/stromal cells (MSCs) are known as the issue in biology because of some unpredictable characteristics in the different microenvironments especially in their bone marrow niche. MSCs are used in the regenerative medicine because of their unique potentials for trans-differentiation, immunomodulation, and paracrine capacity. But, their pathogenic and pro-survival effects in tumors/cancers including hematologic malignancies are indisputable. MSCs and/or their derivatives might be involved in tumor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“… 234 Via releasing microvesicles, LSCs can promote the survival and migration of AML cells and regulate AML malignancy. 247 It has been found that overexpression of miR-34a can inhibit this effect of LSCs by altering the downstream target genes, including caspase-3 and T-cell immunoglobulin mucin-3. miR-34a is a tumor-suppressive molecule associated with AML cell growth and invasion.…”
Section: Signaling Pathways Governing Lsc Maintenancementioning
confidence: 99%
“… 234 Via releasing microvesicles, LSCs can promote the survival and migration of AML cells and regulate AML malignancy. 247 It has been found that overexpression of miR-34a can inhibit this effect of LSCs by altering the downstream target genes, including caspase-3 and T-cell immunoglobulin mucin-3. miR-34a is a tumor-suppressive molecule associated with AML cell growth and invasion.…”
Section: Signaling Pathways Governing Lsc Maintenancementioning
confidence: 99%
“…As we have seen, communication between MM and BM-MSCs cells can take place through mechanisms that can be classified as contact-dependent and/or contact-independent mechanisms[ 115 ]. While the previous section has been dedicated to direct communication mediated by cell adhesion molecules, in this last section we will briefly discuss transport via tunneling nanotubes (TNTs), another form of contact-dependent interaction.…”
Section: Communication Through Contact Dependent Mechanismsmentioning
confidence: 99%
“…In experimental mouse models, it has been shown that VLA-4 blocking antibodies are able to reduce minimal residual disease and favour AML survival [ 135 ]. CXCL12 is just one of several soluble factors (see below) constitutively expressed by MSCs that can stimulate AML cell survival [ 136 , 137 ]. Targeting its CXCR4 receptor (by antagonist or neutralizing antibodies) reduced AML burden and disease progression without affecting HSC engraftment [ 138 ].…”
Section: The Effect Of Leukemic Cells On Mesenchymal Stem Cell Proper...mentioning
confidence: 99%